EFFECTIVENESS OF ROBUSTA COFFEE BEAN EXTRACT GEL (Coffea canephora) ON THE THICKNESS OF COLLAGEN FIBERS AFTER WISTAR RAT TOOTH EXTRACTION - Sari, Desi Sandra; Aisyah, Siti; Rachmawati, Dessy; Sutjiati, Rina; Yuwono, Budi (Odonto : Dental Journal, 2023)
Background: Tooth extraction causes injury to the alveolar bone and oral mucosa which is followed by the body ’s natural response through wound healing. One of the important parameters and indicators of wound healing is collagen density. Collagen is synthesised by fibroblasts in the proliferative phase, which was formed from day 3 and reached its peak on day 7. Robusta coffee beans have active compounds in the form of anti-inflammatory and antioxidants that are effective in accelerating wound healing. Objective: To determine the effectiveness of robusta coffee bean extract gel (Coffea canephora) at concentrations of 12,5%, 25%, and 50% in increasing the thickness of collagen fibres in socket wound healing after tooth extraction in Wistar rats. Method: This type of research is laboratory experimental. The samples used were 40 male Wistar rats divided into 5 groups: negative control, positive control, 12.5% robusta coffee bean extract gel treatment, 25% robusta coffee bean extract gel treatment, and 50% robusta coffee bean extract gel treatment. The sample group was decapitated on the 3rd and 7th day after tooth extraction. Socket tissues were taken to make histological preparations stained with trichrome mallory and then measured using Adobe Photoshop CS 6.0 software. Results: The average thickness of collagen fibres in the Robusta coffee bean extract gel treatment group was higher than that in the control group (p